2012
DOI: 10.1292/jvms.12-0060
|View full text |Cite
|
Sign up to set email alerts
|

Simple Ectopic Kidney in Three Dogs

Abstract: AbSTRACT. Simple ectopic kidney was diagnosed in three dogs by means of radiography and ultrasonography. A 2-year-old castrated male Schnauzer, a 13-year-old female Schnauzer and a 9-year-old male Jindo were referred with vomiting, hematuria and ocular discharge, respectively. In all three dogs, oval-shaped masses with soft tissue density were observed in the mid to caudal abdomen bilaterally or unilaterally, and kidney silhouettes were not identified at the proper anatomic places on abdominal radiographs. Ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Urinary system development is a complicated process of interactions between the embryonic precursors of kidneys, ureters, bladder, and urethra [ 1 ]. Congenital malformations of the urinary system, especially the kidneys, are not the problem commonly described in veterinary medicine, and they are rarely the cause of clinical problems [ 2 , 3 ]. Many authors refer to data from human medicine literature, where kidney malformations are described in more detail than in companion animals such as dogs and cats [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary system development is a complicated process of interactions between the embryonic precursors of kidneys, ureters, bladder, and urethra [ 1 ]. Congenital malformations of the urinary system, especially the kidneys, are not the problem commonly described in veterinary medicine, and they are rarely the cause of clinical problems [ 2 , 3 ]. Many authors refer to data from human medicine literature, where kidney malformations are described in more detail than in companion animals such as dogs and cats [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition has already been reported in humans, swine, dogs, and cats. It is usually rare and asymptomatic (Brückner et al, 2010, Choi et al, 2012Seo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors have suggested that contrasted computed tomography should be performed to identify abnormalities in renal blood supply and ureteral drainage (Seo et al, 2017), the present report corroborates with the literature through contrasted radiography and ultrasonography was possible visualize clearly the presence of both organs fusion. Some authors consider US and excretory urography as the most appropriate exams for detection of crossed renal ectopia with fusion (Allworth and Hoffman, 1999;Brückner et al, 2010;Oliveira et al, 2011;Choi et al, 2012;Mittal et al, 2016). Ultrasonography and excretory urography of the urinary system were effective at diagnosing crossed renal ectopia with fusion, and no advanced imaging techniques were required.…”
mentioning
confidence: 99%
“…Ectopic kidneys were also described in dogs. In three dogs, was found in one case, bilateral ectopic kidneys and in two cases only a left ectopic kidney [4].…”
Section: Resultsmentioning
confidence: 87%
“…An ectopic kidney is often associated with other abnormalities such as: agenesis of the opposite kidney, vascular malformation, and genital anomalies. Ectopic kidneys and an anomalous origin of the renal arteries were described in: the rat [5], dogs [4], a cat [2], a swine [11] and a bovine [9].…”
Section: Introductionmentioning
confidence: 99%